Peroxisome proliferator-activated receptor gamma (PPARG) rs1801282 C>G polymorphism is associated with cancer susceptibility in asians: an updated meta-analysis - Wang, Yafeng (Int J Clin Exp Med, 2015)
Peroxisome proliferator-activated receptor gamma (PPARG) is related to inflammation and plays an important role in the development of cancer. PPARG rs1801282 C>G polymorphism might influence the risk of cancer by regulating production of PPARG gene. Hence, a comprehensive meta-analysis was conducted to explore the association of PPARG rs1801282 C>G polymorphism with cancer susceptibility. An extensive search of PubMed and Embase databases for all relevant publications was carried out. A total of 38 publications with 16,844 cancer cases and 23,736 controls for PPARG rs1801282 C>G polymorphism were recruited in our study. Our results indicated that PPARG rs1801282 C>G variants were associated with an increased cancer risk in Asian populations and gastric cancer. In summary, the findings suggest that PPARG rs1801282 C>G polymorphism may play a crucial role in malignant transformation and the development of cancer.